(untitled) (REMUNOM, 2024)
All over the world, it is common to grow soybeans. The grain is not found every day on the table and in the consumer’s daily life, but, due to the great industrial demand, it is present in the diet in some form. Most of the grains of this grass are processed by various industries, resulting in various products, including oils, milk, vegetable protein, animal meat and even in the manufacture of biofuels. There are several factors that influence global soy consumption, such as the increase in the purchasing power of the population in developing countries, which results in changes in their eating habits. Therefore, this study is an integrated analysis of the literature, having both academic and scientific relevance, in addition to being socially relevant, as it addresses issues related to a new variety of plants for the region, which could be a new source of income for those who depend on of agricultural activities. It is known that soy has a complex production chain in the agribusiness sector, which ranges from the supply of raw materials, sellers, rural producers, resellers, transport and cereal growers, as well as others involved, until it reaches the final consumer. When starting the preparation of this course conclusion work, several sources of research and publications were used, since soybean cultivation is a broad topic and its cultivation is highly sought after, as it is one of the main crops in the country. The items are crucial for the development of agribusiness, especially in the economy. Several production factors and management methods affect soybean progress.